2008
DOI: 10.1111/j.1471-4159.2008.05254.x
|View full text |Cite
|
Sign up to set email alerts
|

Statins reduce neuronal α‐synuclein aggregation in in vitro models of Parkinson’s disease

Abstract: Aggregation of a-synuclein (a-syn) is believed to play a critical role in the pathogenesis of disorders such as dementia with Lewy bodies and Parkinson's disease. The function of a-syn remains unclear, although several lines of evidence suggest that a-syn is involved in synaptic vesicle trafficking probably via lipid binding. Moreover, interactions with cholesterol and lipids have been shown to be involved in a-syn aggregation. In this context, the main objective of this study was to determine if statins -chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 72 publications
(166 reference statements)
5
102
0
2
Order By: Relevance
“…For example, population studies suggested that statin users have signifi cantly lower risk of dementia, including AD ( 2,3 ), and clinical studies suggested that use of statins may also improve other neurological conditions, such as multiple sclerosis, Parkinson's disease, and traumatic brain injury (43)(44)(45)(46)(47). However, some studies of effects of statins on the brain and brain cells suggested that statins have potential not only to promote health but also to induce harm in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, population studies suggested that statin users have signifi cantly lower risk of dementia, including AD ( 2,3 ), and clinical studies suggested that use of statins may also improve other neurological conditions, such as multiple sclerosis, Parkinson's disease, and traumatic brain injury (43)(44)(45)(46)(47). However, some studies of effects of statins on the brain and brain cells suggested that statins have potential not only to promote health but also to induce harm in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been ambivalent evidence in the more distant past, a flurry of recent reports have clarified the detrimental effects of cholesterol accumulation in neurons (30)(31)(32). These studies are paralleled by evidence that increased neuronal cholesterol presents a risk factor for Alzheimer's and Parkinson's diseases (33)(34)(35). Although debated, it has also been proposed that neuronal cholesterol may be due to instrinsic biosynthesis (36), rather than transport from extracellular sources.…”
Section: Metabolic Regulation Via Srebp-2 Inhibition Conveys Neuropromentioning
confidence: 99%
“…Effect of the Cholesterol on AS Binding-Cholesterol is an important component of cellular membranes (57,58) and also affects the binding of AS to membranes and the rate of AS aggregation (59,60). We analyzed the effect of cholesterol on the AS-membrane binding.…”
Section: As Labeling and Labelmentioning
confidence: 99%